Kahlo - Souter, Gerry (Parkstone International, 2012)
Behind Frida Kahlo's portraits, lies the story of her life -- a body of work drawn from cries of anger and fury, blended into a potent, and artistically exceptional, combination. At six years of age, she suffered a bout of polio, and she was just 18 when a terrible bus accident changed her life forever, leaving her handicapped and burdened with constant physical pain. But her explosive character, raw determination and hard work helped to shape her artistic talent. Frida Kahlo managed to forge a place for herself in the macho society of Mexico, despite the double handicap of her crushed body and.